Letras obreras. Clase trabajadora y experiencia urbana en la escritura proletaria. Chile, primer cuarto del siglo XX - Jorge Navarro López (Les Cahiers ALHIM)
The article aims to study the urban experience of the working class by analysing the narrative that workers produced and published in the workers' press. Workers' literature was not only concerned with politics and ideology but also with the projections, values and visions of the urban proletariat's experience. Through the analysis of the proletarian poetic and narrative production, the aim is to delve into the everyday life, meanings, imagination, aesthetic preferences, and the popular way of life, which are fundamental dimensions of working-class culture in the first quarter of the 20th century.